ADOLESCENT HEALTH IN FAMILY MEDICINE: A REVIEW OF SCREENING TOOLS AND PREVENTIVE APPROACHES - Dr. Raya Khudhair Mohsin (European Science Publishing, 2025)
Adolescent health in family remedy calls for a balanced integration of effective screening equipment and preventive strategies to cope with the complex biopsychosocial needs of this populace. This systematic evaluate evaluates proof-based totally procedures for optimizing adolescent care in primary care settings, that specialize in screening efficacy, preventive interventions, and implementation demanding situations. A complete seek throughout PubMed, Scopus, and Cochrane Library (2010–2023) identified 52 research assembly inclusion standards, analyzed the usage of PRISMA tips and GRADE proof excellent frameworks. Key findings spotlight the utility of brief, tested tools including the CRAFFT (89% sensitivity for substance use) and PHQ-nine (88% sensitivity for depression) in high-volume clinics, along the effectiveness of preventive techniques like college-primarily based nutrients programs and motivational interviewing. Challenges consisting of issuer training deficits, cultural obstacles to disclosure, and fragmented referral pathways were recurrent subject matters, disproportionately affecting marginalized organizations. The assessment proposes actionable tips, which include standardized adolescent fitness curricula for family physicians, technology-greater screening structures, and policy reforms to incentivize preventive care repayment. By synthesizing modern-day proof, this painting presents a roadmap for clinicians and policymakers to bridge gaps in adolescent health care, emphasizing the centrality of circle of relative's medication in fostering equitable, lifelong well-being.
Keywords: Adolescent Health - Family Medicine - Screening Tools - Preventive Care - Mental Health.